Incidence of Microorganism in Different Rooms of Science Department (Research Journal of Padmakanya Multiple Campus, 2024)
Microbes are found everywhere in our environment even inside a laboratory. Among different contamination in laboratory, the most common biological contaminants are microbial contaminants with bacteria, molds, yeasts, viruses, algae and protozoa. So, contamination during working in laboratory became the biggest problem due to unwanted grown of microorganism which create false positive result. Therefore, this study was carried out from March 2022 to May 2022 with the aim to explore the total microbial count. Plates exposing technique was done for the count of bacteria and fungi from different rooms of science department which were Laboratory (6), class rooms (4) and office room (2). From the settle plate method, bacteria and fungi were isolated and identified. Among bacterial isolates, Citrobacter spp., Bacillus spp., S. aureus., and E. coli were identified and among fungal isolates, Aspergillus spp., Penicillum spp., Rhizopus spp. and Fusarium spp. were identified. This study concluded that from science department, different bacteria and fungi were isolated in which MDR bacteria were also isolated which is one of a biggest global concern. Therefore, the laboratory and the rooms should be disinfected regularly.